Block of voltage-gated calcium channels by peptide toxins. (December 2017) - Bourinet, Emmanuel; Zamponi, Gerald W.
Abstract: Venoms from various predatory species, such as fish hunting molluscs scorpions, snakes and arachnids contain a large spectrum of toxins that include blockers of voltage-gated calcium channels. These peptide blockers act by two principal manners - physical occlusion of the pore and prevention of activation gating. Many of the calcium channel-blocking peptides have evolved to tightly occupy their binding pocket on the principal pore forming subunit of the channel, often rendering block poorly reversible. Moreover, several of the best characterized blocking peptides have developed a high degree of channel subtype selectivity. Here we give an overview of different types of calcium channel-blocking toxins, their mechanism of action, channel subtype specificity, and potential use as therapeutic agents. This article is part of the Special Issue entitled 'Venom-derived Peptides as Pharmacological Tools.' Highlights: Toxins from fish hunting molluscs produce pore blockers of calcium channels. Peptide toxins from arachnids often mediate gating inhibition of calcium channels. Peptides from animal venom may have therapeutic potential.